DETERMINANT OPINI AUDIT GOING CONCERN ON COMPANIES LISTED ON IDX PERIOD 2015-2017 - Dewi Murdiawati; Ellen Theresia Sihotang (Prosiding International conference on Information Technology and Business (ICITB), 2019)
The aim of this study is to analyze determinants of going concern audit opinion. The independent variable that use in this study are profitability which measured by return on asset, company growth which measured by sales growth, debt default which measured by dummy variable and stock emision strategy which also measured by dummy variable, while dependent variable that use in this study is going concern audit opinion which measured by dummy variable. Sample of this study is mining company, basic sector and chemical that listed in www.idx.co.id for the period 2015-2017. The technique of data analysis that use in this study is logistic regression analysis with SPSS 23.0 For Windows Program. The result of this study explain that profitability and stock emision strategy have influence to going concern audit opinion, while company growth and debt default have influence to going concern audit opinion.Keywords: profitability, company growth, debt default, stock emision strategy, and going concern audit opinion